Asiaticoside ameliorates uterine injury induced by zearalenone in mice by reversing endometrial barrier disruption, oxidative stress and apoptosis - Ge Gao; Hongyang Jiang; Hai Lin; Hongfeng Yang; Ke Wang (BMC, 2024)
Abstract Zearalenone (ZEA) is a mycotoxin produced by Fusarium fungi that has been shown to have adverse effects on human and animal health, particularly on the fertility of females. As a saponin derived from the medicinal plant Centella asiatica, asiaticoside (AS) has multiple bioactivities. This study aimed to investigate the protective effects of AS on ZEA-induced uterine injury and the underlying mechanism. In the present study, we demonstrated that AS could rescue ZEA-induced uterine histopathological damage and modulate the secretion of sex hormones, including progesterone (P4), luteinizing hormone (LH), and estradiol (E2), in ZEA-treated mice. Moreover, AS alleviated ZEA-induced damage to endometrial barrier function by upregulating the expression of tight junction proteins (ZO-1, occludin, and claudin-3). Further mechanistic investigations indicated that ZEA reduces the antioxidant capacity of uterine tissues, whereas AS improves the antioxidant capacity through activating the Nrf2 signaling pathway. Most notably, the protective effect of AS was blocked in Nrf2 gene knockout (Nrf2−/−) mice. Moreover, the p38/ERK MAPK pathway has been implicated in regulating ZEA toxicity and the beneficial effect of AS. Additionally, an Nrf2 inhibitor (ML385) weaken the suppressive effect of AS on the oxidative stress and MAPK pathway. AS also inhibits ZEA-induced apoptosis in uterine tissues via the PI3K/Akt signaling pathway. However, when the PI3K small molecule inhibitor LY294002 was co-administered, the ability of AS to suppress the expression of apoptosis-related proteins and inhibit ZEA-induced apoptosis decreased. Collectively, these findings reveal the involvement of multiple pathways and targets in the protective effect of AS against ZEA-induced uterine injury, providing a new perspective for the application of AS and the development of a ZEA antidote.